Contested commemorations : republican war veterans and Weimar political culture - Ziemann, Benjamin (Cambridge : Cambridge University Press, 2013)
'This innovative study of remembrance in Weimar Germany analyses how experiences and memories of the Great War were transformed along political lines after 1918. Examining the symbolism, language and performative power of public commemoration, Benjamin Ziemann reveals how individual recollections fed into the public narrative of the experience of war. Challenging conventional wisdom that nationalist narratives dominated commemoration, this book demonstrates that Social Democrat war veterans participated in the commemoration of the war at all levels: supporting the'no more war' movement, mourning the fallen at war memorials and demanding a politics of international solidarity. It describes how the moderate Socialist Left related the legitimacy of the Republic to their experiences in the Imperial army and acknowledged the military defeat of 1918 as a moment of liberation. This is the first comprehensive analysis of war remembrances in post-war Germany and a radical reassessment of the democratic potential of the Weimar Republic'--
Machine generated contents note: Introduction; 1.'A short period of insight': symbolizing defeat as liberation, 1918-1923; 2. Republican war memories: the Reichsbanner Black Red Gold; 3. The personal microcosm of Reichsbanner activism; 4. Public commemorations and republican politics; 5. In search of a national symbol, 1924-1933; 6. Pacifist veterans and the politics of military history; 7. Mass media and the changing texture of war remembrance, 1928-1933; Conclusion; Bibliography.
Includes bibliographical references (p. 280-305) and index.
Keywords: World War, 1914-1918 -- Veterans -- Germany; World War, 1914-1918 -- Influence; World War, 1914-1918 -- Personal narratives, German; World War, 1914-1918 -- Social aspects -- Germany; Veterans -- Germany -- History -- 20th century; Political culture -- Germany -- History -- 20th century; War memorials -- Germany -- History -- 20th century; Memory -- Political aspects -- Germany -- History -- 20th century; Germany -- Politics and government -- 1918-1933.; Germany -- Social conditions -- 1918-1933.